Simulations of the latitudinal variability of CO‐like and OCS‐like passive tracers below the clouds of Venus using the Laboratoire de Météorologie Dynamique GCM. Issue 10 (3rd October 2013) - Marcq, E.; Lebonnois, S.
<x xml:space="preserve">Abstract</x> [1] The lower atmosphere of Venus below the clouds is a transitional region between the relatively calm lowermost scale height and the superrotating atmosphere in the cloud region and above. Any observational constraint is then welcome to help in the development of general circulation models of Venus, a difficult task considering the thickness of its atmosphere. Starting from a state‐of‐the‐art 3‐D Venus General Circulation Model (GCM), we have included passive tracers in order to investigate the latitudinal variability of two minor gaseous species, carbonyl sulfide (OCS) and carbon monoxide (CO), whose vertical profiles and mixing ratios are known to vary with latitude between 30 and 40km. The relaxation to chemical equilibrium is crudely parametrized through a vertically uniform time scale τ. A satisfactory agreement with available observations is obtained with 108s≲τCO≲5·108 s and 107s≲τOCS≲108 s. These results, in addition to validating the general circulation below the clouds, are also helpful in characterizing the chemical kinetics of Venus' atmosphere. This complements the much more sophisticated chemical models which focus more on thermodynamical equilibrium.